Odpowiedzi

Najlepsza Odpowiedź!
2010-03-17T20:08:15+01:00
2y-5x=6
-x=-y+6
2y - 5 x = 6
y - x = 6 | *-2
2y - 5x = 6
-2y +2x = -12
- 3 x = - 6
x = 2

b}
2x-5(y+1)=-5
-x+2(y+2)=4
2x - 5y + 5 = -5
-x - 2y = 4-4 | *-2
2x - 5 y = 0
-2x + 4y = 0
-y = 0


d) 3x+y=4
6x-(1-2y)=7
3x+y=4 / *-2
6x + 2 y = 7 + 1
- 6 x - 2 y = -8
0=0




4 3 4
2010-03-17T20:14:24+01:00
A)
∫2y-5x=6
∫-x=-y+6|:(-1)

2y-5x=6
x=y-6

2y-5(y-6)=6
2y-5y+30=6
-3y=6-30
-3y=-24
y=8

x=y-6
x=8-6
x=2




b)
∫2x-5(y+1)=-5
∫-x+2(y+2)=4

2x-5y-5=-5
-x+2y+4=4

2x-5y=0
-x+2y=0|:(-1)

2x-5y=0
x=2y

2*2y-5y=0
4y-5y=0
-y=0
y=0

x=2*0
x=0



c)
∫2y-(3+y)=0
∫-x+y/2=2|*2

2y-3-y=0
-2x+y=4

y=3
-2x+3=4
-2x=4-3
-2x=1
x=-½



d)
∫3x+y=4
∫6x-(1-2y)=7

3x+y=4
6x-1+2y=7

3x+y=4
6x+2y=8|:2

3x+y=4
y=4-3x

3x+4-3x=4
0=0
brak rozwiązań


7 4 7
2010-03-17T20:16:51+01:00
A) 2y-5x=6
-x=-y+6 /*(-1)

2y-5x=6
x=y-6

2y-5(y-6)=6

2y-5y +30 =6

-3y = -24 /:(-3)
y= 8

-x=-y+6
-x= -8+6
-x= -2 /*(-1)
x=2

b)2x-5(y+1)=-5
-x+2(y+2)=4

2x- 5y -5 = -5
-x+2y+4 = 4

2x -5y=0
-x = -2y /*(-1)

2x -5y=0
x=2y

2*2y -5y=0
4y-5y=0
-y=0
y=0

x=2y
x=0

c)2y-(3+y)=0
-x+y/2=2

2y -3 - y=0
y= 3


-x+3/2 =2
-x =1/2
x= -1/2

d)3x+y=4
6x-(1-2y)=7

y= -3x+4
6x-1+2y=7

6x+2y=8
y= -3x+4

6x+2(-3x+4)=8
6x-6x+8=8
0=0
układ sprzeczny



1 5 1